2014
DOI: 10.1108/mf-06-2013-0131
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study on the dynamic relationship between oil prices and Indian stock market

Abstract: Purpose – This study aims to investigate the dynamic relationships between oil price shocks and Indian stock market. Design/methodology/approach – The study used daily data for the period starting from January 2001 to March 2013. In this study, Johansen's cointegration test, vector error correction model (VECM), Granger causality test, impulse response functions (IRFs) and variance decompositions (VDCs) test have been applied to exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…Ko and Lee point out that the relationship between uncertainty in international economic policy and stock prices is usually negative, however that it changes over time [18]. From January 2001 to March 2013, Nath Sahu et al showed that there is a long-term relationship between oil and India's stock market [19]. They also confirm that there is no checking variable between short-term causality and reveal that a positive shock to oil prices has a small but sustained positive impact on Indian stocks in the short term.…”
Section: Introductionmentioning
confidence: 99%
“…Ko and Lee point out that the relationship between uncertainty in international economic policy and stock prices is usually negative, however that it changes over time [18]. From January 2001 to March 2013, Nath Sahu et al showed that there is a long-term relationship between oil and India's stock market [19]. They also confirm that there is no checking variable between short-term causality and reveal that a positive shock to oil prices has a small but sustained positive impact on Indian stocks in the short term.…”
Section: Introductionmentioning
confidence: 99%
“…We have identified the following four most important research gaps in the existing literature. Firstly, in existing literature number of research articles have only explored linear linkages between stock indexes, exchange rate fluctuations, oil price volatilities, and gold prices by utilizing linear models like VECM (Badry, 2019;Keswani & Wadhwa, 2018;Neveen, 2018;Rajesh, 2019;Sahu et al, 2014;Shiva & Sethi, 2015), VAR (Areli Bermudez Delgado et al, 2018;Ghulam, 2018;Huang et al, 2018), ARDL modeling approach (Ho, 2018;Singhal et al, 2019) and limited efforts have been made to explore the asymmetrical impact of Exchange rates-Gold-Oil price volatility on stock indexes by using NARDL model by (Shin et al, 2014).…”
Section: Research Gapsmentioning
confidence: 99%
“…Bhunia (2013) investigated the co-integration relationship among crude oil prices, domestic gold price and stock price indices in India and found that there exists a long term relationship among selected variables. Sahu et al (2014), studied the impact of changed crude oil prices on stock markets and found a long term co-integrating relationship between these two variables and volatility of crude oil price affects the volatility of stock prices in India. Bhat (2014) studied the linear and nonlinear causal nexus between oil price shocks and sock returns in India using standard VAR model and Diks and Panchenko (2006) frameworks and found the evidence of unidirectional causality from stock returns to crude oil price changes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…High interest cost further will subdue corporate earnings and also attract investors towards bond markets leading to fall in stock prices (Kapusuzoglu, 2011). India is having a very meager production of crude oil and maximum of requirement is filled up through imports from OPEC countries (Sahu et al, 2014). Gisser and Goodwin (1986) argued that crude oil being an important input used in production of many goods and services, an increase in price of the crude will affect the cash flow of firms.…”
Section: Introductionmentioning
confidence: 99%